Association between Smoking Habit and Pulmonary Tuberculosis at Dr. Soetomo General Academic Hospita - Balivia Andi Permata Hapsari; Prastuti Asta Wulaningrum; Rimbun Rimbun (Biomolecular and Health Science Journal, 2021)
Introduction: Smoking has been reported as one of tuberculosis (TB) risk factor. The association between smoking and TB has been proven in multiple studies, but little known about the association between smoking degree and sputum smear positive. Methods: An analytic observational study using cross-sectional design. Data of patients with pulmonary TB conducted at DOTS (Directly Observed Treatment Short course)/MDR (Multi Drug Resistance) outpatient and inpatient ward in Dr Soetomo General Hospital Surabaya from January to October 2018. The degree of smoking was measured using Brinkman Index (BI). The odds ratio (OR) and 95% confidence intervals (CI) were also estimated.Results: There were 94 patients with pulmonary TB, 56 non-smoker and 38 smoker. Light smoking (P = 0,120, OR = 0.200, 95% CI: 0.022-1.823), moderate smoking (P=0.377, OR = 1.667, 95% CI: 0.533-5.209), heavy smoking (P=0.076, OR= 0.333, 95% CI: 0.96-1.160). Moderate smoking compared to heavy smoking as a control (P=0.33, OR = 5.000, 95% CI=1.096-22.820). Conclusion: There’s no significant correlation between smoking habits and sputum smear positive, but the present study evidenced the patients with smoking habits had greater chance to get sputum smear positive than non-smokers. Patient with moderate smoking compared to heavy smoking had greater chance to get sputum smear positive.